Polarization signatures and brightness temperatures caused by horizontally oriented snow particles at microwave bands: Effects of atmospheric absorption. Issue 12 (26th June 2015) - Xie, Xinxin; Crewell, Susanne; Löhnert, Ulrich; Simmer, Clemens; Miao, Jungang
Abstract This study analyzes the effects of atmospheric absorption and emission on the polarization difference (PD) and brightness temperature (TB) generated by horizontally oriented snow particles. A three‐layer plane‐parallel atmosphere model is used in conjunction with a simplified radiative transfer (RT) scheme to illustrate the combined effects of dichroic and nondichroic media on microwave signatures observed by ground‐based and spaceborne sensors. Based on idealized scenarios which encompass a dichroic snow layer and adjacent nondichroic layers composed of supercooled liquid water (SCLW) droplets and water vapor, we demonstrate that the presence of atmospheric absorption/emission enhances TB and damps PD when observed from the ground. From a spaceborne perspective, however, TB can be reduced or enhanced by an absorbing/emitting layer above the snow layer, while a strong absorbing/emitting layer below the dichroic snow layer may even enhance PD. The induced PD and TB, which rely on snow microphysical assumptions, can vary up to 2 K and 10 K, respectively, due to the temperature‐dependent absorption of SCLW. RT calculations based on 223 snowfall profiles selected from European Centre for Medium‐Range Weather Forecasts data sets indicate that the existence of SCLW has a noticeable impact on PD and TB at three window frequencies (150 GHz, 243 GHz, and 664 GHz) during snowfall. Our results imply that while polarimetric channels at the three window channels have the potential for snowfall characterization, accurate information on liquid water is required to correctly interpret the polarimetric observations.